Assessing Multiple Benefits of Community-Based Ecotourism: Evidence from Annapurna Conservation Area Project (ACAP) Region, Kaski District - Pasa, Rajan Binayek; Shrestha, Suman Kumar (The Third Pole: Journal of Geography Education, 2024)
This study analyzes multiple benefits of community-based ecotourism in the ACAP region, located in Kaski District. The research focuses on the economic, social, cultural, environmental, educational, and health benefits of community-based ecotourism. A crosssectional survey design was used to collect data from 234 tourism entrepreneurs through self-administered questionnaires. The findings suggest that ecotourism has contributed significantly to local economies, generating substantial annual income, creating employment opportunities, and fostering the economic growth of local communities. Ecotourism has been shown to positively influence family income, household expenditure, and overall economic stability among tourism entrepreneurs. The study also highlights the broader social and cultural impacts, with increased awareness and engagement in conservation efforts, as well as improvements in community health and education. The involvement of the communities in tourism entrepreneurship has further strengthened the link between ecological preservation and economic benefits, creating a sustainable model of rural development. Overall, the research underscores the growing importance of ecotourism as a key driver of rural livelihood improvement in the ACAP region. The findings suggest that ecotourism is not only a source of income but also a means of enhancing community resilience, environmental stewardship, and cultural preservation. The study advocates for the continued promotion and development of ecotourism by government agencies, emphasizing its role in achieving long-term multiple benefits of community-based ecotourism in the potential areas of the country.